Elements of discrete mathematics numbers and counting, groups, graphs, orders and lattices - Diekert, Volker 1955-; Hertrampf, Ulrich 1956-; Kufleitner, Manfred; Rosenberger, Gerhard 1944- (De Gruyter textbook, 2024)
This book treats the elements of discrete mathematics that have important applications in computer science, thus providing the necessary tools for the reader to come to a competent mathematical judgement of modern developments in the age of information. Almost all assertions are shown with full proofs. Exercises are provided, with solutions presented in full detail